Constituição de práticas de numeramento em eventos de tratamento da informação na educação de jovens e adultos - Priscila Coelho Lima (2007)
This research analyzes the mobilization and constitution of numeracy practices in events of Treatment of the Information in the Young and Adult Education. For that, we followed an opinion research by students of the Projeto de Ensino Fundamental de Jovens e Adultos da UFMG Segundo Segmento (PROEF-2 Fundamental Teaching Project for Young and Adult of UFMG Second Part), activity linked to Projeto Nossa Escola Pesquisa sua Opinião (NEPSO Our School Researches Your Opinion Project). We observed, specially, the meetings in which students dedicated themselves to counting, treatment and organization of the data produced by the proposed research, in order to identify strategies, questionings, inferences and conclusions elaborated within and for the processing of produced information. Therefore, we analyze numeracy practices mobilization and constitution in the confrontation of students expectations, knowledge and experiences with other students experiences and concepts, and with school mathematical knowledge and in the elaboration of relations with the quantification, impregnated with political, social, economic and cultural values.